2024
DOI: 10.1021/acs.accounts.3c00638
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop Nickel Catalysis Invigorated by Electron-Deficient Diene Ligands

Camille Z. Rubel,
Wen-Ji He,
Steven R. Wisniewski
et al.

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Due to the rarity of precious metals like palladium, nickel catalysis is becoming an increasingly important player in organic synthesis, especially for the formation of bonds with sp 3 -hybridized carbon centers. Traditionally, catalytic processes involving active Ni( 0) species have relied on Ni(COD) 2 or in situ reduction of Ni(II) salts. However, Ni(COD) 2 is an air-and temperature-sensitive material that requires use in an inertatmosphere glovebox, and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…To gain insight into the viability of using iminophosphorane ligands in high energy photochemical conditions (365 nm) with open shell species generated via hydrogen atom transfer (HAT) catalysis, we explored the use of MacMillan's metallaphotoredox method 62 for direct arylation of C(sp 3 )–H bonds ( Scheme 6C ). Gratifyingly, irradiation of mixtures containing 2-trifluoromethyl-5-bromopyridine (58) and cyclohexane (59) in the presence of tetrakis(tetrabutylammonium)decatungstate (( n -Bu 4 N) 4 [W 10 O 32 ], TTBADT), Ni(COD)(DQ) 63 and iminophosphorane 31 with 365 nm provided the desired product 60 in useful yields.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the viability of using iminophosphorane ligands in high energy photochemical conditions (365 nm) with open shell species generated via hydrogen atom transfer (HAT) catalysis, we explored the use of MacMillan's metallaphotoredox method 62 for direct arylation of C(sp 3 )–H bonds ( Scheme 6C ). Gratifyingly, irradiation of mixtures containing 2-trifluoromethyl-5-bromopyridine (58) and cyclohexane (59) in the presence of tetrakis(tetrabutylammonium)decatungstate (( n -Bu 4 N) 4 [W 10 O 32 ], TTBADT), Ni(COD)(DQ) 63 and iminophosphorane 31 with 365 nm provided the desired product 60 in useful yields.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Engle and co-workers reported that Ni(cod)(dq) (DQ: duroquinone) ( 2 ) was available as a catalyst precursor for several nickel(0)-catalyzed synthetic reactions as a surrogate of Ni(cod) 2 because of its much improved stability to oxidation and thermal decomposition. 12,18,19 It was also shown that the employment of Ni(cod)(dq) ( 2 ) along with an appropriate ligand showed comparable reactivities to Ni(cod) 2 ( 1 ) in several coupling reactions such as Suzuki–Miyaura coupling, Buchwald–Hartwig amination, etc . However, despite the remarkable breakthroughs in nickel catalysts, there are surprisingly few reports of their subsequent utilization in catalytic synthetic reactions (Chart 1).…”
Section: Introductionmentioning
confidence: 99%